Engineered 2D Transition Metal Dichalcogenides—A Vision of Viable Hydrogen Evolution Reaction Catalysis. Issue 16 (4th March 2020) - Lin, Liangxu; Sherrell, Peter; Liu, Yuqing; Lei, Wen; Zhang, Shaowei; Zhang, Haijun; Wallace, Gordon G.; Chen, Jun
Abstract: The hydrogen evolution reaction (HER) is an emerging key technology to provide clean, renewable energy. Current state‐of‐the‐art catalysts still rely on expensive and rare noble metals, however, the relatively cheap and abundant transition metal dichalcogenides (TMDs) have emerged as exceptionally promising alternatives. Early studies in developing TMD‐based catalysts laid the groundwork in understanding the fundamental catalytically active sites of different TMD phases, enabling a toolbox of physical, chemical, and electronic engineering strategies to improve the HER catalytic activity of TMDs. This report focuses on recent progress in improving the catalytic properties of TMDs toward highly efficient production of H2 . Combining theoretical and experimental considerations, a summary of the progress to date is provided and a pathway forward for viable hydrogen evolution from TMD driven catalysis is concluded. Abstract : Building on the fundamental understanding of the catalytic process and advancements in chemical, electronic, and structural tuning of transition metal chalcogenides, the key concepts for the electrochemical hydrogen evolution reaction (HER) are provided and their potential as the next‐generation of HER catalysts is discussed, providing a clear pathway forward for viable hydrogen evolution.